Physiology of human endocrine system: a review from Islamic perspective - Abdul Ghani, Radiah; Mohd Rosli, Nur Athirah; Zainuddin, Zainul Ibrahim; Ikmal Hisham, Ahmad Irfan (2016)
Apart from many scientific studies conducted on human structure and function, there is a growing need to analyse such knowledge from Islamic perspective. Thus, the aim of this paper is to review and integrate between scientific knowledge and Islamic view on one of the important system in human body, which is endocrine system. The scientific data collection was extracted from the publications such as scientific journals and books which are published from 1990 onwards. While the Islamic perspective was related to the scientific data based on eleven framework of analysis; Tawhidic view and the principles and objectives of the shari’ah. The analysis and integration of human endocrine system from Islamic perspective was explored on the physiological changes on melatonine release, tahajjud prayer and its beneficial on our system and how affectionate touch promotes bonding, and the endocrine signaling that reflects the character of best people. The finding is expected to invite in mine to think and appreciate further the perfection of the creation of Almighty Allah.